2000 - 2020) Saving in the Syrian economy and its relationship to some economic variables - قابقلي ابتهال (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Most economic studies agree that saving is the basis of economic growth and development in every society, whether it is advanced or underdeveloped, and the saving awareness is absent from a society that only lives in underdevelopment. A study of the reality of saving in the Syrian economy, and the relationship of saving to some economic variables such as investment, inflation and GDP during the period (2000 - 2020) was studied, in light of the war that Syria has been witnessing since 2011, which left effects on all macroeconomic indicators